Trend Of Dengue in A Tertiary Care Hospital of Surat City, Western India - Arun Tank; Mannu R Jain (Medsci Publications, 2012)
Background: India is one of the countries in the South-East Asia region regularly reporting dengue fever (DF)/dengue hemorrhagic fever (DHF) outbreaks. Objective: To study the trend of confirmed dengue cases admitted in a tertiary care hospital & to identify the seasonal variation of the disease during three years period in Surat city, Western India. Methodology: Secondary analysis of data of Dengue patients obtained from three hospitals of Surat city was done. Results: 1918 serum samples were tested for dengue IgM ELISA out of which 671 samples tested positive. Majority were males, having sex ratio of 2.54:1 and in the age group of 15-44 years. Maximum number of cases were seen in 2009, 393 and in the month of October, 125. Conclusion: The numbers of cases declined during this study period. Community awareness, early diagnosis and management and vector control measures were strengthened which results in decrease in number of cases.